Bioethics : 50 Puzzles, Problems, and Thought Experiments - Aas, Sean D.; O'Neil, Collin; Lepora, Chiara (New York : Routledge, 2024)
Bioethics: 50 Puzzles, Problems, and Thought Experiments collects 50 cases--both real and imaginary--that have been, or should be, of special interest and importance to philosophical bioethics. Cases are collected together under topical headings in a natural order for an introductory course in bioethics. Each case is described in a few pages, which includes bioethical context, a concise narrative of the case itself, and a discussion of its importance, both for broader philosophical issues and for practical problems in clinical ethics and health policy. Each entry also contains a brief, annotated, list of suggested readings. In addition to the classic cases in bioethics, the book contains discussion of cases that involve several emerging bioethical issues: especially, issues around disability, social justice, and the practice of medicine in a diverse and globalized world. Key Features: Gives readers all chapters presented in an identical format: The Case Responses Suggested Readings Includes reference to up-to-date literature in journals devoted both to more generalist ethics and to bioethics Offers short and self-contained chapters, allowing students to quickly understand an issue and giving instructors flexibility in assigning readings to match the themes of the course Features actual or lightly fictionalized cases in humanitarian aid, offering a type of case that is often underrepresented in bioethics books Authored by three scholars who are actively involved in the central research areas of bioethics
IntroductionPart I: Bioethics and Philosophical Methodology1. Bioethics as Moral Theory: The Transplant and the Trolley2. Bioethics as Metaphysics: The Brain Transplant3. Bioethics across Cultures: The FarewellPart II: Creating Life4. Should I have Children? The Islanders and the Cube5. Which Children Should I Have, I? The Non-Identity Problem6. Which Children Should I have, II? Gattaca7. Making People Happy, or Making Happy People? The Repugnant Conclusion8. Is Abortion Permissible? Thomson's Violinist9. What we Owe to our Unborn Children: Rescues Easy and HardPart III:Value of Life: Disability and Well-Being10. Is it bad to be disabled, I? The case of Cara and Daisy11. Is it bad to be disabled, I? Adaptive Preference12. Morbidity vs. Mortality: The QALY trap13. What makes a disability? the Counterfactual Test14. When is a life worth living? The Challenge of Covert ConsciousnessPart IV: Deciding for Others15. Deciding for disability: The Ashley Treatment16. Dilemmas of decision-making: Kill Mary to Save Jodie?17. Deciding for the Future: Margo's Advance Directive18. My decision alone? Family, Community, and Consent in Global ContextPart V: Deciding for Yourself19. Wrongs, without Harms? Two cases on the basis of informed consent20. Who is Competent to Consent? Anorexia Nervosa21. The Ethics of Influence, I: A Clinical Nudge22. The Ethics of Influence, II: The Nocebo EffectPart VI: Killing and Dying23. Better to Die? The 'Mercy' Killing at Memorial24. To Kill or Let Die? Rachels on Active and Passive Euthanasia25. What Does It Mean to Kill? Stopping hearts, Artificial and Otherwise26.Counting Deaths:Statistical and Identified Lives27. What Does It Mean to Die, I? Jahi McMath and the Definition of Death28. What Does It Mean to Die, II? Death and the Sanctity of the Body in IslamPart VII: The Ethics of Clinical Research29. When Is Research Ethical? The Tuskegee Study30. Using or Misusing? The Short-Course AZT Trials31. What can Consent Justify? Challenge Trials for COVID-1932. A Right to Try? Access to Experimental MedicinePart VIII: Fair Distribution33. Do the Numbers count? Taurek's Tradeoffs34. Ours or Us? Henrietta Lacks, and the HeLa Cell Line35. Allocation in an Emergency: Ventilator Triage36. Data and Distribution: Algorithmic Fairness37. Fairness in the Clinic: The Racial Empathy GapPart IX: Public Health: Freedom and Justice38. Fair Access to Care, or Freedom of Conscience? Physician Refusals39. Stay at home? The Ethics of Lockdowns40. Freedom and Viruses: The Case of Medical Misinformation41. My Body, My Choice? Vaccine MandatesPart X: The Boundaries of Medicine42. What Should We Change? The Yeshiva Student and His Orientations43. Can Medicine Make us Better? The God MachinePart XI: Medicine across Borders: Dilemmas of Complicity and Compromise44. Does it Harm to Help? Rescuing Migrants45. Who Owns My Image? Photographing Survivors46. Harm Minimization I: Female Genital Cutting47. Harm Minimization II: Physicians and Caning48. Doing the Best with What We have? Foreign Medicine and the Haiti Earthquake49. How to keep helping, I: Taking Sides in the Arab Spring?50. How to keep helping, II: Compromise with the Taliban
Keywords: Bioethics; PHILOSOPHY / General